Endogenous quality choice, signaling, and welfare - LEE, Gea M. (Institutional Knowledge at Singapore Management University, 2016)
We consider a model in which each worker endogenously selects his own type through aprivate investment decision and selects a public signal in the labor market. Signaling thencontributes to social welfare through its influence on the quality choice. We offer a rationalefor the argument that there are too many high-type workers from a welfare perspective,identifying circumstances under which separating equilibrium generates too many high-typeworkers while having to use the incentive-compatible signal and treat high-type workersdifferently in the market. The inefficiency can then be reduced in pooling equilibrium.